Creation Of Prematurely Born Infant Airways Model Based On X-Ray Ct And Mri Scans - Lázňovský, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
Proposed contribution deals with the creation of infants’ airway model, based on available clinical MRI and CT scans of newborns. For this purpose, an algorithm which extracts the airway geometry was developed. Resulting geometry is consequently transformed to the airway model in stereolithography format, suitable for further analysis. The algorithm was tested on the data which correspond to an infant born in 30 weeks of gestation and scanned 14 days after birth. Thus, the model corresponds to the 32 weeks old infant.
Keywords: Airway model; Neonatology; Medical imaging; Image processing